Subjektiv skriving med utgangspunkt i psykisk helsearbeid - Fagerland, Tone (Nordisk Tidsskrift for Helseforskning, 2014)
When writing a scientific essay, it is necessary for the author herself to be visible. In the case of writing in and about mental health work, this means that the intuitive perspective of the writer/practitioner be attended to.  The aim of this process is the development of theory that is grounded in reflection upon lived experience and the narratives of practice. In this sense, it is perhaps necessary to take up a perspective informed by the human sciences since this perspective is one that can fully make space for the ethical, aesthetic and empirical considerations.